Effect of different drying methods on phytochemicals and antioxidant properties of unfermented and fermented teas from Sabah Snake Grass (Clinacanthus nutans Lind.) leaves - A. B., Mohd Fadzelly; A.Z, Zaleha; M., Hasmadi; M, Lusia Barek (International Food Research Journal, 2015)
Clinacanthus nutans (Burm. F.) Lindau or locally known in Sabah, Malaysia as ‘Sabah Snake Grass’ has been ethnobotanically used to treat various diseases in Asian countries. This study was conducted to determine the total phenolics content (TPC), flavonoids content (TFC) and antioxidant activity of herbal teas developed from C. nutans leaves with different drying techniques (microwave-oven dried and freeze dried) and infusion time (1, 2, 5, 10, 15 and 20 min). Ferric reducing/antioxidant power (FRAP) assay, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS) and 2, 2-diphenyl-1-pycryl-hydrazyl (DPPH) free radical scavenging assays were used to investigate the antioxidant capacity. The highest TPC of herbal tea was observed in 20 min infusion of unfermented microwave-oven dried leaves (177.80 ± 19.10 mg TAE/L), while the highest TFC was observed in 10 min infusion of fermented microwave-oven dried leaves (22.13 ± 1.53 mg CE/L). Short infusion times from 5 min to 15 min were able to extract high amount of phenolics compounds. Unfermented tea contained higher TPC content (P < 0.05) as compared to fermented tea, while, TFC showed no significant difference between both types. Freeze dried infusion shows no significant difference (P > 0.05) as compared to microwave-oven dried for TPC, TFC and antioxidant capacity. Moderate and low correlation was observed between TPC and FRAP values (r = 0.507) and between TFC and ABTS values (r = 0.256). Preparation of C. nutans herbal tea as potential natural antioxidant source can be used as a basic reference for future research on the dietary intake of these herbal teas.